Corporate Governance Dalam Mendeteksi Kecurangan Laporan Keuangan - Utomo, Sasongko Tri, Dr. Syamsudin, SE, MM, Imronudin SE,M.Si, Ph D (2017)
This study aimed to look at corporate governance in detecting fraudulent financial statements. Corporate governance is discussed by proxy of foreign ownership, domestic ownership, public ownership. Proxy in detecting fraud reports by using the formula Beinesh model where the model of Fraud Financial Statement occurs when the value of <-2.22 and otherwise > -2.22 happen Fraud Financial Statement. And moderating variables with firm size as measured by total assets. The sample used for as many as 694 manufacturing companies with the period 2011-2015. The sampling technique purposive sampling method. Data were analyzed using logistic regression analysis with a model of moderation. The findings indicate that direct ownership structure proxy foreign ownership, domestic ownership, and public ownership has a negative and significant impact on the fraud financial statement. In the proxy firm size total assets have significant positive effect on financial statement fraud. After moderated by total assets the result show that there is significantly stronger and more negative impact between ownership structure, foreign ownership, domestic ownership, and public ownership to the fraud financial statement.